Aircraft noise monitoring using multiple passive data streams. (March 2016) - Aldeman, M; Bacchus, R; Chelliah, K; Patel, H; Raman, G; Roberson, D
Monitoring of aircraft in the skies surrounding an airport is important to ensure the safety of the aircraft as well as quality of life for nearby residents. The traditional method of tracking aircraft position involves the ubiquitous rotating active radar, and the traditional method of monitoring aircraft noise is the single omnidirectional microphone. Both of these systems have significant disadvantages. In the past several decades, microphone array acoustic monitoring systems have become widely known although they are typically practical only for research purposes. More recently, advanced beamforming algorithms have set the stage for much smaller compact microphone arrays. Meanwhile, the Automatic Dependent Surveillance-Broadcast position tracking system has quickly risen in popularity. In this study, an advanced compact microphone array is used along with Automatic Dependent Surveillance-Broadcast and more conventional methods to monitor and track aircraft that are approaching and departing Chicago's Midway Airport. The systems are portable and compact, and the unified streams of data can more fully characterize an individual aircraft, offering distinct advantages over existing monitoring systems.